The complete chloroplast genome of Gaillardia pulchella Foug. and its phylogenetic analysis - Hongqin Li; Jicheng Yuan; Guiyuan Wu; Liqiang Wang (Mitochondrial DNA. Part B. Resources)
Gaillardia pulchella, an annual Asteraceae herb native to tropical America, is widely cultivated in China for its vibrant blooms and long flowering period. The species exhibited notable biological activities, including antioxidant and anti-inflammatory effects. We presented the first complete chloroplast genome of G. pulchella, spanning 151,778 bp with an overall GC content of 37.7%, and containing 128 genes (85 protein-coding genes, 35 tRNA genes, and eight rRNA genes). Phylogenetic analysis revealed its close relationship with Galinsoga parviflora, Tagetes erecta, and Flaveria bidentis. This study provided valuable genomic insights for evolutionary studies, and potential pharmaceutical applications of G. pulchella.